1H NMR and multivariate data analysis of the differences of metabolites in five types of dry-cured hams. (November 2018) - Zhang, Jian; Ye, Yangfang; Sun, Yangying; Pan, Daodong; Ou, Changrong; Dang, Yali; Wang, Ying; Cao, Jinxuan; Wang, Daoying
Abstract: In order to distinguish the taste styles of dry-cured hams (Jinhua, Xuanwei, Country, Parma and Bama), we established a 1 H nuclear magnetic resonance spectroscopy method to identify metabolites. Totally, 33 charged metabolites, including amino acids, organic acids, nucleic acids and their derivatives, sugars, alkaloids and others were identified. The abundant glutamate, lysine, alanine, leucine and lactate could be the major contributors of taste. Total variables were explained by PC1 (67.7%) and PC2 (16.0%) which showed that Parma and Xuanwei styles were close to each other (similar amino acids, peptide, organic acids and alkaloids contents). Bama style showed the highest PC1 and amino acids, organic acids and alkaloids contents. Country style was located on the left-most area of PC1 (the lowest amino acids, organic acids and peptide, but the highest sugars contents). Sensory evaluation revealed that Bama ham had the highest overall taste score, followed by Jinhua, Parma, Xuanwei and American Country ham. We concluded that the proportions and combinations of taste components explained the specific taste instead of any single component. These findings provided a better understanding of different metabolomics among hams. Graphical abstract: Highlights: The metabolites profile of different types of dry-cured hams were different. Amino acids could be major contributors to the taste of dry-cured hams. The proportions and combinations of metabolites explained the specific taste of hams. NMR provided a profile of major metabolites to distinguish different types of hams.